2021
DOI: 10.1093/cid/ciab262
|View full text |Cite
|
Sign up to set email alerts
|

Day at the Races: Comparing BioFire FilmArray Blood Culture ID Panels With Verigene Blood Culture Panel in Gram-Negative Bloodstream Infections Using DOOR-MAT Analysis

Abstract: Three RDT platforms (Verigene BC-GN, BioFire® BCID, and BCID 2 (RUO)) were compared using the Desirability of Outcome Ranking Management of Antimicrobial Therapy (DOOR -MAT) to evaluate potential downstream antimicrobial prescribing decisions resulting from the panels different organism and resistance detection. BioFire BCID (RUO) had the best mean DOOR-MAT scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Further studies in a multicenter setting are warranted to determine the usefulness and possible problems of the BCID2, especially concerning its effect on patient management and outcomes. In fact, a recent study showed, in a retrospective analysis, a superiority of BCID2 to BCID1 and Verigene BC-Gram negative for theoretical optimal antimicrobial prescribing decisions ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in a multicenter setting are warranted to determine the usefulness and possible problems of the BCID2, especially concerning its effect on patient management and outcomes. In fact, a recent study showed, in a retrospective analysis, a superiority of BCID2 to BCID1 and Verigene BC-Gram negative for theoretical optimal antimicrobial prescribing decisions ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A new version of this assay has been recently released (BioFire Blood Culture Identification 2 Panel, bioMerieux, France) resulting in a broader panel including 33 pathogens (26 bacterial genera/species and 7 fungal species) and 10 resistance markers; few studies have evaluated the performance of BCID2 on clinical samples so far [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the DOOR MAT approach include an examination 41 of treatment of E. coli and Klebsiella pneumoniae bloodstream infections at the Veteran's Health Administration and a comparison 42 of potential effect of different rapid diagnostic platforms on antimicrobial prescribing. As a metric of antibiotic prescribing appropriateness, this analysis approach could be complementary to antimicrobial stewardship programs wanting to measure quality of prescriptions in addition to the typical metrics that mainly address quantity of prescriptions (e.g., days of therapy).…”
Section: Door Matmentioning
confidence: 99%